Investor-state dispute settlement and impact on investment rulemaking - United Nations; United Nations Conference on Trade and Development (New York : United Nations, 2007)
"As demonstrated by this paper, the experience with the investor-state dispute settlement of a number of countries (mostly in the Asia-Pacific region) appears to have influenced the development of new international investment agreements (IIAs) by those countries. Observing how previous IIAs were interpreted and applied by arbitral tribunals, their governments have come up with new provisions and new language, which address most of the problems that arose in the context of investment disputes."--Publisher description
"UNCTAD/ITE/IIA/2007/3."--T.p. verso.
"Sales no.: E.07.II.D.10."--T.p. verso.
Includes bibliographical references (p. [97]-102).
Available both in print and online.
Keywords: Convention on the Settlement of Investment Disputes between States and Nationals of Other States -- (1965); North American Free Trade Agreement -- (1992 December 17); Investments, Foreign (International law); Dispute resolution (Law); Arbitration (International law)